Pengaruh Kualitas Produk, Citra Merek dan Harga Terhadap Keputusan Pembelian Konsumen di Kopi Male Kabupaten Situbondo - Ismail, Andi Muhammad; Qur’ani, Syifa Fauzia; Gemaputri, Ariesia Ayuning; Andini, Paramita (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This research is motivated by the increasing number of new drink shops that are appearing, one of which is coffee drink products. The company that produces coffee drinks in the city of Situbondo is Kopi Male. This research aims to analyze and test the influence of product quality, brand image and price on consumer purchasing decisions at Kopi Male, Situbondo Regency. The population in this study were all consumers who purchased coffee beverage products at Kopi Male with a sample of 40 respondents. The analytical tool used in this research is multiple linear regression analysis with the help of SPSS 22.00. The results of this research can be concluded that the variables product quality (X1), brand image (X2) and price (X3) simultaneously have a significant influence on consumer purchasing decisions (Y) at Kopi Male Situbondo Regency. Partially, the results of this research can be concluded that the product quality (X1) and price (X3) variables have a significant effect on consumer purchasing decisions at Kopi Male, Situbondo Regency, while the brand image variable (X2) has an insignificant effect on consumer purchasing decisions (Y) at Kopi Male. Situbondo Regency. The price variable (X3) is the variable that has the dominant influence on consumers' purchasing decisions (Y) at Kopi Male, Situbondo Regency.